ANALISIS VALUE AT RISK MENGGUNAKAN SIMULASI MONTE CARLO UNTUK BERINVESTASI DI CRYPTOCURRENCY ETHEREUM DAN BINANCE COIN DI MASA PANDEMI - Siswanto, Rickhy (UNIB Press, 2023)
The purpose of this research is to conduct a risk analysis using a Monte Carlo simulation by assessingwhether investing in cryptocurrencies during the COVID-19 pandemic, especially in Ethereum andBinance Coin, which have become the prima donna in the crypto sector lately, have received maximuminvestment returns. And also a little assess whether in the future these two cryptocurrency assets arealso worth trading in Indonesia. During this pandemic, many people began to care about the importanceof investment after many companies had difficulty funding and then they started laying off a lot ofworkers because of the difficulty of getting into the stock exchange in Indonesia. In Indonesia, there aremany start-ups or growing companies to raise funds through digital asset cryptocurrency platforms suchas Ethereum and Binance Coin by writing a smart contract to bridge a contract with investors.